Plinia peruviana (Poir.) Govaerts (jabuticaba) extract inhibits the development of gastric ulcers in animal models through gastroprotective mechanisms - Isabel Sousa Alcântara; Renata Torres Pessoa; Lucas Yure Santos da Silva; Roger Henrique Souza da Costa; Aparecida Barros da Silva; Tarcisio Mendes Silva; Samara Alves Brito; Anita Oliveira Brito Pereira Bezerra Martins; Jean Carlos Pereira Sousa; Andréa Rodrigues Chaves; Ricardo Neves Marreto; Francisco Sandro Menezes Rodrigues; et al. (Food Bioscience, 2026)

Type-specific sensitivity versus detection breadth in HPV diagnostics: improved analytical detection of HPV16/18 by nested PCR - Yago Tomaz Vieira da Silva; Larissa Alves Honorato Ferreira; Samara Fontes de Lima Gomes; Beatriz Helena Dantas Rodrigues De Albuquerque; Maryana Thalyta Ferreira Câmara De Oliveira; Alice Dantas Leite; José Veríssimo Fernandes; Ricardo Ney Oliveira Cobucci; Daniel Carlos Ferreira Lanza (Archives of Virology, 2026)
Accurate detection of high-risk human papillomavirus (HPV) is central to cervical cancer screening. Current diagnostic strategies increasingly prioritize broad-spectrum assays to maximize genotype coverage. However, theoretical genotype breadth does not necessarily translate into effective sample-level detection when clinically dominant targets are present at low copy number. Here, we evaluated this analytical trade-off using conventional PCR as a controlled experimental framework. Type-specific nested PCR assays targeting HPV16 and HPV18 were developed and applied to 41 cervical samples. Nested PCR showed markedly higher relative analytical sensitivity than single-round amplification and produced a greater proportion of specific and interpretable detections than the broad-spectrum consensus systems tested here (MY09/11 and GP5/6). HPV16 and/or HPV18 DNA was detected by nested PCR in 22/41 samples, whereas MY09/11 and GP5/6 detected 11/41 and 2/41 samples, respectively, under the tested conditions. These findings indicate that broad genotype coverage and effective detection of positive samples are distinct analytical properties. In settings where prevalent HPV targets occur at low abundance, a highly sensitive genotype-focused assay may reveal more target-positive samples than a broader but less sensitive consensus approach. The results are not intended to replace clinically validated broad-spectrum screening assays, but they support explicit preservation of per-target analytical sensitivity in reflex testing and future multi-target HPV assay design.

Degradability, Phytotoxicity, and Life Cycle Assessment of Chestnut Waste Biocomposites - Simão B. Silva; Samara Rodrigues; Elena Surra; Elsa Vieira; Cristina Delerue-Matos; Olga M. Freitas; Valentina F. Domingues (Environmental Processes, 2026)

Biodegradation assessment of polymer-based films by bacterial species in the marine environment and its correlation with microplastic production and toxicity - Márcia Priscila Porto dos Santos; Natália de Albuquerque Vita de Abreu; Franciele Saorin; Tarcisio Camlofski; William Alves; Desiree Schuck; Camila Suliani Raota; Samara Letiele dos Santos; Letícia Steckel; Daniela Rodrigues Araujo; Wanessa Ramsdorf; Felipe Vannucchi de Camargo; et al. (Journal of Hazardous Materials, 2025)

Retrospective analysis of sperm metrics in fresh ejaculates of collared peccaries presenting contrasting semen freezability - Samara Sandy Jerônimo Moreira; Romário Parente dos Santos; Luana Grasiele Pereira Bezerra; Ana Glória Pereira; Náyra Rachel Nascimento Luz; Andreza Vieira Brasil; Thales Pinheiro Cavalcanti; Moacir Franco de Oliveira; Simone Maria Massami Kitamura Martins; André Furugen Cesar de Andrade; Alexandre Rodrigues Silva (Cryobiology, 2025)

Mycobacterial infections in cats and a dog: A case series from Southern Brazil and one health implications - Bibiana Campello Moglia Dutra; Anelise Bonilla Trindade-Gerardi; Gabriela da Cruz Schaefer; Samara Christina França de Almeida; Bruna Correa Lopes; Cristine Cerva; Deisy Daiana Lerner; Matheus Viezzer Bianchi; Angélica Cavalheiro Bertagnolli Rodrigues; Rogério Oliveira Rodrigues; Gabriela Hartmann; David Driemeier; et al. (Veterinary Research Communications, 2025)

Sequential use of nutritional additives in diets for finishing Nellore young bulls in confinement on the carcass and meat characteristics - Paulo Eduardo de Oliveira Monteiro; Jaqueline Rodrigues Ferreira Cara; Lucy Mery Antonia Surita; Marília Williani Filgueira Pereira; Bruno Henrique de Sousa Limoni; Thiago Luís Alves Campos de Araújo; Rosanne Cristine da Silva Luz Benev Santos; Samara Miyaki Corrêa; Priscilla Dutra Teixeira; Luís Carlos Vinhas Ítavo; Marina de Nadai Bonin Gomes (Tropical Animal Health and Production, 2025)

Feline botulism: two decades and two reports - Ísis Assis Braga; Nicoly Ferreira de Urzedo; Guilherme Oliveira Maia; Ana Paula Carvalho Gomes; Raiany Borges Duarte; Bruna Samara Alves-Ribeiro; Andressa da Silva Martins; Tamires Ataides Silva; Luiz Henrique Barbosa Pires; Stéfanne Rodrigues Rezende; Nathalia de Assis Pereira; Raquel Loren dos Reis Paludo; et al. (Veterinary Research Communications, 2025)

Histological alterations in placentas of normal and anomalous pups: correlation with neonatal outcomes and fetal health - Laura M. Lovo; Marina Vilela Estevam; Samara Beretta; Amanda Marmol; Loren M. Pasqui; Fernanda A. Rodrigues-Silva; Renata O. Barreto; Alessandre Hataka; Gilson Hélio Toniollo; Maria Lúcia G. Lourenço; Maricy Apparício (Theriogenology, 2025)

Microencapsulation of Pediococcus pentosaceus using cupuassu flour-based as wall material: Application and impact on petit suisse cheese - Katherine Gutiérrez-Álzate; Gabriele de Abreu Barreto; Bruna Samara S. Rekowsky; Letícia Alencar Pereira Rodrigues; Deborah Murowaniecki Otero; Marion Pereira da Costa (Food Bioscience, 2025)

Cytotoxic activity, phenolic content, and fatty acid of brown algae from tropical reefs - Samara Rodrigues; Elizabeth Fernanda de Oliveira Borba; Marllyn Marques da Silva; Fábio Henrique Galdino dos Santos; Noemia Pereira da Silva Santos; Terezinha Gonçalves da Silva; Fungyi Chow; Daniela Maria do Amaral Ferraz Navarro; Emerson Peter da Silva Falcão; Sonia Maria Barreto Pereira (Brazilian Journal of Botany, 2025)
New cancer therapies development is a huge demand. This research evaluated cytotoxic activity against normal and cancer cells of brown algae (Dictyotales) extracts with high antioxidant activity. Canistrocarpus cervicornis , Dictyopteris delicatula and Lobophora variegata extracts from two beaches of Pernambuco were obtained by two serial maceration method: 1° Extraction—dichloromethane and methanol (2:1 v/v) and subsequently water at 60 °C; 2° Extraction—dichloromethane and methanol (2:1 v/v), subsequently ethanol and finally water at 80 °C. Phenolic compounds and cytotoxicity against normal cell lines L-929 (murine fibroblast), PBMC (human peripheral blood mononuclear cells) and J774A1 (mouse macrophages), and cancer cell lines P815 (murine mastocytoma), S-180 (murine Sarcoma), NCI-H292 (human lung mucoepidermoid carcinoma), HCT-116 (human colorectal carcinoma), JUKART (human T cell leukaemia) and MCF-7 (human breast adenocarcinoma) were assessed. Only for L-929 strain, among normal cells, extracts presented cytotoxicity. Organic extracts showed moderate to high cytotoxic activity against P815, MCF-7 and HCT-116 cancer cell lines. Organic extract L. variegata Jaguaribe 2° Extraction exhibited the best cytotoxic activity with high IC 50 values (28–35 µg/mL). Thus, we evaluate its acids profile that showed important polyunsaturated fatty acids and carboxylic acid, such as arachidonic acid and cinnamic acid that is being reported to L. variegata for the first time. Various research demonstrated the anticancer activity of this substance. Therefore, the high cytotoxic activity of our most active extract could be due to the presence of fatty acids and carboxylic acid, acting synergically, including cinnamic acid. These results encourage macroalgae use as an anticancer metabolites source for human therapies.

Vertical flow constructed wetlands for swine wastewater treatment: Impacts of the deposit layer on hydraulic performance and treatment efficiency - Mateus Piovesan; Gabriela Anzanello Rodrigues; Bryan Brummelhaus de Menezes; Marcus Soares; Raphael Corrêa Medeiros; Gracieli Fernandes; Samara Terezinha Decezaro (Journal of Water Process Engineering, 2025)

Sex differences in the orofacial antinociceptive effect of metformin and the role of transient receptor potential channels - Sacha Aubrey Alves Rodrigues Santos; Marina de Barros Mamede Vidal Damasceno; Barry John Sessle; Antônio Eufrásio Vieira-Neto; Gerlânia de Oliveira Leite; Francisco Ernani Alves Magalhães; Kaio César Simiano Tavares; Samara Casemiro Benevides; Adriana Rolim Campos (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Reevaluating the role of secondary metabolites in cadmium phytoremediation - Augusto César Rodrigues; Samara Requena Nocchi; Jorge Raposo Luiz; Valter Aragão do Nascimento; Carlos Alexandre Carollo (Environmental Monitoring and Assessment, 2025)

Impact of Storage on In Vitro Permeation and Mucoadhesion Setup Experiments Using Swine Nasal Mucosa - Jaiza Samara Macena de Araújo; Gabriela Gama Xavier Augusto; Aylla Mesquita Pestana; Francisco Carlos Groppo; Flávia Sammartino Mariano Rodrigues; Pedro Duarte Novaes; Michelle Franz-Montan (AAPS PharmSciTech, 2024)

Investigating cryopreservation techniques for maintaining morphology and in vitro viability of cartilage and skin from Spix’s yellow-toothed cavies (Galea spixii Wagler, 1831) for conservation through biobanks - Samara Lima Olindo; Leonardo Vitorino Costa de Aquino; Yasmin Beatriz França Moura; Yara Letícia Frutuoso e Silva; Ana Lívia Rocha Rodrigues; Vinicius Dantas da Silva; Alexsandra Fernandes Pereira (Journal of Molecular Histology, 2024)

The Commerson's dolphin as Subantarctic sentinel of POPs: Insights into the pollutant status in one of the southernmost coastal areas of the globe - Iris Cáceres-Saez; Elitieri Santos-Neto; Guillermo Cassini; Bárbara Manhães; Samara Rodrigues dos Santos; Nara de Oliveira-Ferreira; H. Luis Cappozzo; José Lailson Brito (Environmental Pollution, 2024)

Global patterns and predictors of primary freshwater crab richness across taxa and realms - Douglas Fernandes Rodrigues Alves; Pablo Ariel Martinez; Célio Magalhães; Samara de Paiva Barros-Alves; Ariádine Cristine de Almeida; Talita Ferreira Amado (Hydrobiologia, 2024)

Climatic niche evolution and speciation modes in the transisthmian Alpheus shrimps (Caridea: Alpheidae) - Douglas Fernandes Rodrigues Alves; Pablo Ariel Martinez; Samara de P. de Barros‐Alves; Ariádine Cristine de Almeida; Marco Aurélio Mendes Elias; Carla Hurt; Kristin M. Hultgren (Journal of Biogeography, 2024)
Aim We studied the niche evolution and diversification modes in transisthmian Alpheus shrimps by examining the interplay between environmental niche divergence and conservatism in allopatric sister species. In a broader perspective, the current study analysed the evolution of climatic niche and the role of the environment in species diversification of Alpheus transisthmian shrimp. Location Atlantic and Eastern‐Pacific oceans. Taxon Alpheus shrimps (Caridea: Alpheidae). Methods We assembled georeferenced occurrences for 33 species of Alpheus (with 24 sister species) from a time‐calibrated molecular phylogeny. We modelled their ecological niches and assessed niche overlap through pairwise comparisons. Additionally, we performed phylogenetic reconstructions of the ancestral environmental niche, for each niche axis. Results Our results demonstrate that thermal tolerances, food availability and hydrodynamic forces were relevant environmental axes in evolutionary processes in transisthmian species of Alpheus . Among the 528 paired comparisons, we found that most niches were divergent, including in 12 clades formed by pairs of sister species (in only two of these clades were the niches fully equivalent). Phylogenetic reconstructions of ancestral niches showed an initial niche conservatism in all axes, with divergences intensifying in the last 12 million years. Main Conclusions We found evidence that confirms the relevance of the environmental changes that occurred in the West Atlantic and East Pacific for niche evolution in transisthmian Alpheus species, as well as for the emergence of some lineages. Our findings provide evidence for different modes of Alpheus species speciation in a period consistent with the closure of the Isthmus of Panama.

Assessment of toxicity of pyriproxyfen, Bacillus thuringiensis, and malathion and their mixtures used for mosquito control on embryo-larval development and behavior of zebrafish - Renata Meireles Oliveira Padilha; Samara da Silva Gomes; Jadson Freitas da Silva; Renatta Priscilla Ferreira Silva; André Lucas Corrêa de Andrade; Amanda Rodrigues dos Santos Magnabosco; Thamiris Pinheiro Santos; Andressa Raphaely de Lima Silva; Maria Leticia Santos Carnaúba da Silva; Marilia Ribeiro Sales Cadena; Pabyton Gonçalves Cadena (Environmental Science and Pollution Research, 2024)

Antimicrobial efficiency of bromhexine hydrochloride against endometritis-causing Escherichia coli and Trueperella pyogenes in bovines - Bruna Matzembacker; Dyeison da Silva Fantinel; Claudia Medeiros Rodrigues; Samara Pereira da Silva; Matheus Henrique Dal Bó Marin; Danillo Sales Rosa; Mateus Matiuzzi da Costa; Simone Silveira; Lilian Kolling Girardini (Brazilian Journal of Microbiology, 2024)

The Plata plume water penetration into the southwestern Atlantic shelf during the Holocene - Gabrielle Dias Bonifatto; Samara Cazzoli y Goya; Edilson de Oliveira Faria; Irys Martins Rodrigues Ventura; Mascimiliano de los Santos Maly; Renata Hanae Nagai; Michel Michaelovitch de Mahiques (Geo-Marine Letters, 2024)

Biodegradable PBAT/PLA blend films incorporated with turmeric and cinnamomum powder: A potential alternative for active food packaging - Layara L.R.L. de Castro; Lauriene G.L. Silva; Iago R. Abreu; Cristiano J.F. Braz; Samara C.S. Rodrigues; Regilda S. dos R. Moreira-Araújo; Rudy Folkersma; Laura H. de Carvalho; Renata Barbosa; Tatianny S. Alves (Food Chemistry, 2024)

Species distribution models to predict the impacts of environmental disasters on shrimp species of economic interest - Wanessa Gomes Pereira; Ariádine Cristine de Almeida; Samara de Paiva Barros-Alves; Douglas Fernandes Rodrigues Alves (Marine Pollution Bulletin, 2024)

Effects of climate change and mixtures of pesticides on the Amazonian fish Colossoma macropomum - Samara Silva de Souza; Kerem Hapuque Rodrigues Bruce; Jaqueline Custódio da Costa; Desyree Pereira; Grazyelle Sebrenski da Silva; Adalberto Luis Val (Science of The Total Environment, 2024)

Allometric models for non-destructive estimation of the leaflet area in acai (Euterpe oleracea Mart.) - Samara K. A. de Sousa; Rodrigo G. M. Nascimento; Flavio Henrique S. Rodrigues; Rafael G. Viana; Lucas C. da Costa; Hugo A. Pinheiro (Trees, 2024)

Effects of different subcutaneous sites on heterotopic autotransplantation of canine ovarian tissue - Fabiana AS Brandão; Danielle CC de Brito; Leda MC Pereira; Kele A Alves; Lucy VS Ñaupas; Samara S de Souza; Duanny M de S Cunha; Reginaldo P de S Filho; Benner G Alves; Ana PR Rodrigues; Dárcio IA Teixeira (Veterinary Research Communications, 2023)

An iota-carrageenan isolated from marine alga Agardhiella ramosissima negatively modulates the inflammatory response in arthritis conditions - Lucas Henrique Marques Rodrigues; Francisco Fábio Bezerra de Oliveira; Francisco Felipe Bezerra; Samara Rodrigues Bonfim Damasceno Oliveira; Rudy Diavila Bingana; Luana David do Carmo; Márcia Rúbia Silva Melo; Luciano de Sousa Chaves; André Luiz dos Reis Barbosa; Jand-Venes Rolim Medeiros; Pedro Marcos Gomes Soares; Paulo Antônio de Souza Mourão; et al. (Bioactive Carbohydrates and Dietary Fibre, 2023)

Broodstock management of the arrow crab Stenorhynchus seticornis and effects of temperature and salinity on larvae survival - Mariana Antunes; Samara de Paiva Barros-Alves; Douglas Fernandes Rodrigues Alves; Rafael Augusto Gregati; Maria Lucia Negreiros-Fransozo (Aquaculture International, 2023)

Giants of the Amazon: How does environmental variation drive the diversity patterns of large trees? - Robson Borges de Lima; Eric Bastos Görgens; Diego Armando S. da Silva; Cinthia Pereira de Oliveira; Anderson Pedro B. Batista; Rinaldo L. Caraciolo Ferreira; Flavia R. C. Costa; Renato A. Ferreira de Lima; Perseu da Silva Aparício; Jadson Coelho de Abreu; José Antônio Aleixo da Silva; Aretha Franklin Guimaraes; et al. (Global Change Biology, 2023)
For more than three decades, major efforts in sampling and analyzing tree diversity in South America have focused almost exclusively on trees with stems of at least 10 and 2.5 cm diameter, showing highest species diversity in the wetter western and northern Amazon forests. By contrast, little attention has been paid to patterns and drivers of diversity in the largest canopy and emergent trees, which is surprising given these have dominant ecological functions. Here, we use a machine learning approach to quantify the importance of environmental factors and apply it to generate spatial predictions of the species diversity of all trees (dbh ≥ 10 cm) and for very large trees (dbh ≥ 70 cm) using data from 243 forest plots (108,450 trees and 2832 species) distributed across different forest types and biogeographic regions of the Brazilian Amazon. The diversity of large trees and of all trees was significantly associated with three environmental factors, but in contrasting ways across regions and forest types. Environmental variables associated with disturbances, for example, the lightning flash rate and wind speed, as well as the fraction of photosynthetically active radiation, tend to govern the diversity of large trees. Upland rainforests in the Guiana Shield and Roraima regions had a high diversity of large trees. By contrast, variables associated with resources tend to govern tree diversity in general. Places such as the province of Imeri and the northern portion of the province of Madeira stand out for their high diversity of species in general. Climatic and topographic stability and functional adaptation mechanisms promote ideal conditions for species diversity. Finally, we mapped general patterns of tree species diversity in the Brazilian Amazon, which differ substantially depending on size class.

From wasted ferric sludge to valuable waste: a systematic review using the knowledge development process—constructivist method - Iana Chaiene de Araujo Vidal; Elisângela Maria Rodrigues Rocha; Arthur Marinho Cahino; Samara Teixeira Pereira; Amanda Gondim Cabral Quirino; Raqueline Caldas do Nascimento (Environment, Development and Sustainability, 2023)

Anti-inflammatory and anti-necrotic effects of lectins from Canavalia ensiformis and Canavalia brasiliensis in experimental acute pancreatitis - Samara Rodrigues Bonfim Damasceno Oliveira; Álvaro Xavier Franco; Marielle Pires Quaresma; Cecília Mendes Morais de Carvalho; Fabrícia da Cunha Jácome Marques; Patrícia da Silva Pantoja; Vanessa Azevedo Mendonça; Vinicius José da Silva Osterne; Jorge Luis Almeida Correia; Ana Maria Sampaio Assreuy; Marcellus Henrique Loiola Pontes de Souza; Kyria Santiago do Nascimento; et al. (Glycoconjugate Journal, 2022)

Development of a Nanoformulation for Oral Protein Administration: Characterization and Preclinical Orofacial Antinociceptive Effect - Marina de Barros Mamede Vidal Damasceno; Sacha Aubrey Alves Rodrigues Santos; João Ronielly Campêlo Araújo; Lana Karine Vasconcelos Barroso; Samara Casemiro Benevides; Francisco Ernani Alves Magalhães; Kaio César Simiano Tavares; Renato de Azevedo Moreira; Ana Cristina de Oliveira Monteiro-Moreira; Angelo Roncalli Alves e Silva; Adriana Rolim Campos (AAPS PharmSciTech, 2022)

The structure of shallow water fish assemblages in sandy beaches of a tropical bay in the southwestern Atlantic - Samara Macedo Pinto; Cassiano Monteiro-Neto; Elisabete Barbarino; Rafael de Almeida Tubino; Marcus Rodrigues da Costa (Ichthyological Research, 2022)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Brachyuran crab (Crustacea, Decapoda) assemblage associated with Sargassum cymosum in southeastern Brazil - Samara de P. Barros-Alves; Douglas Fernandes Rodrigues Alves; Valter José Cobo (Marine Biodiversity, 2018)

Morphometric differences between two exotic invasive freshwater caridean species (genus Macrobrachium ) - Thiago Elias da Silva; Douglas Fernandes Rodrigues Alves; Samara de P. Barros-Alves; Ariádine Cristine Almeida; Fabiano Gazzi Taddei; Adilson Fransozo (Invertebrate Reproduction & Development, 2018)

Reproductive output of the ornamental shrimp Lysmata vittata (Stimpson, 1860) (Decapoda: Caridea) in wild populations and under different maturation diets - Andréa Santos e Almeida; Samara de Paiva Barros-Alves; Gustavo Luis Hirose; Douglas Fernandes Rodrigues Alves (Invertebrate Reproduction & Development, 2018)

The mating system of the symbiotic pea-crab Dissodactylus crinitichelis (Brachyura, Pinnotheridae): monogamy or promiscuity? - Douglas Fernandes Rodrigues Alves; Gustavo Luis Hirose; Samara de P. Barros-Alves; J. Antonio Baeza (Marine Biology, 2017)

Energy and protein requirements of non-descript breed hair lambs of different sex classes in the semiarid region of Brazil - Rafael Torres de Souza Rodrigues; Mario Luiz Chizzotti; Samara Rodrigues Martins; Ivonete Ferreira da Silva; Mário Adriano Ávila Queiroz; Tiago Santos Silva; Karina Costa Busato; Aderbal Marcos de Azevêdo Silva (Tropical Animal Health and Production, 2016)

Carcass and non-carcass component yields of crossbred Boer and Brazilian semiarid indigenous goats subjected to different feeding levels - Samara Rodrigues Martins; Mario Luiz Chizzotti; Sandra Mari Yamamoto; Rafael Torres de Souza Rodrigues; Karina Costa Busato; Tiago Santos Silva (Tropical Animal Health and Production, 2014)

Onset of sexual maturity and relative growth of the freshwater crab Trichodactylus fluviatilis (Trichodactyloidea) in south-eastern Brazil - Daniel José Marcondes Lima; Valter José Cobo; Douglas Fernandes Rodrigues Alves; Samara de Paiva Barros-Alves; Vivian Fransozo (Invertebrate Reproduction & Development, 2013)